Effect of a longitudinal electric field on helicon wave propagation in InSb - Pandey N.L.; Singh R.N. (My University, 2025)
The dispersion equation accounting for the effect of a parallel electric field in an n-type semiconductor plasma has been derived. The propagation of helicon waves through InSb at low temperature has been studied. The parallel electric field is found to defocus the propagating helicon waves in InSb. The propagation of helicon waves in InSb depicts the onset of electric-field-induced instability. This shows that the helicon waves under suitable conditions would grow while propagating through the bulk specimen. The diagnostic role of heliconwave propagation has been discussed. © 1976 The American Physical Society.